1980
DOI: 10.1177/030089168006600307
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Treatment of Loco-Regional Breast Cancer Recurrences: Critical Considerations on 120 Cases

Abstract: In the present study we report the long-term results for 120 female patients who underwent mastectomy for breast cancer, from 1955 to 1965, and in whom the first relapse was represented by a skin recurrence or a supraclavicular lymph node metastastis. Eighty-nine patients had been submitted only to local therapy, 11 had also undergone bilateral oophorectomy, and in the remaining 20 hormonal compounds had been administered in addition to local therapy. The disease-free interval between the first and the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In the past, breast cancer patients who developed an isolated local recurrence were considered to have an unfavorable prognosis since the majority of these patients would eventually succumb to distant metastatic disease. Surgery, radiation therapy, or both were considered the treatment of choice for locoregional control, but treatment with these modalities conferred no benefit in terms of DFS for this patient population (4–8,17–19). For this reason, studies were begun to evaluate whether systemic therapy administered to patients in whom locoregional control had been achieved would improve DFS and decrease the incidence of distant metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, breast cancer patients who developed an isolated local recurrence were considered to have an unfavorable prognosis since the majority of these patients would eventually succumb to distant metastatic disease. Surgery, radiation therapy, or both were considered the treatment of choice for locoregional control, but treatment with these modalities conferred no benefit in terms of DFS for this patient population (4–8,17–19). For this reason, studies were begun to evaluate whether systemic therapy administered to patients in whom locoregional control had been achieved would improve DFS and decrease the incidence of distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Only a limited amount of information exists on the natural history of the disease and the results of systemic therapy in patients with stage IV‐NED disease, and most of the studies have focused on the effect of local treatment on patient survival. Several studies have shown that approximately 30–40% of patients with a local or regional recurrence will develop systemic disease within 3 months (1–8) and that 50–80% of these patients will develop systemic disease within 2 years. The 5‐year survival rate ranges from 4% to 36% according to different retrospective studies (2,4,7,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, local treatment with these modalities does not improve DFS for this patient population. 4,8,[23][24][25] This suggests that many of these patients have micrometastases at the time of their first recurrence. Consequently, studies were initiated to assess whether adequate local treatment to achieve Stage IV-NED followed by systemic therapy would improve long-term outcome for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,7,9 To our knowledge, few studies published to date have considered the role of adjuvant systemic treatment in patients with recurrent breast carcinoma who have been rendered Stage IV-NED with surgery and/or radiotherapy. We previously reported the results from three Phase II studies of doxorubicin-based chemotherapy for Stage IV-NED breast carcinoma in anthracycline-naïve patients that were conducted between 1974 and 1992.…”
mentioning
confidence: 99%